The role of ear environment in postharvest susceptibility of maize to toxigenic Aspergillus flavus - Mutiga, Samuel K.; Chepkwony, N.; Hoekenga, O.A.; Flint-Garcia, S.A.; Nelson, R.J. (Wiley, 2019)
A kernel screening assay (KSA) was used to assess the genetic and environmental effects on the vulnerability of maize to aflatoxin accumulation. Kernels of 26 inbred lines that had been grown in seven environments, and 190 lines of the Intermated B73xMo17 (IBM) population grown in one location in the United States, were inoculated with a toxigenic strain of A. flavus and incubated in the dark at 30°C for 6 days. Percent kernel colonization (PKC), sporulation and aflatoxin were influenced by the maize genotypes (G), the location (“ear environment” or E) and the GxE interactions. Overall, low broad‐sense heritabilities were observed for PKC, sporulation and aflatoxin. PKC was significantly correlated with sporulation in all environments. Aflatoxin was positively correlated with colonization for two and with sporulation for all ear environments. Higher grain sulphur or magnesium in IBM was associated with less colonization or aflatoxin. Postharvest susceptibility of maize to aflatoxin is thus influenced by factors that are modulated by the ear environment. In a KSA, sporulation could be a proxy test for aflatoxin accumulation.